Expression of exosomal microRNAs during chondrogenic differentiation of human bone mesenchymal stem cells. Issue 1 (11th September 2018) - Sun, Hao; Hu, Shu; Zhang, Ziji; Lun, Jiayong; Liao, Weiming; Zhang, Zhiqi
Abstract: The aim of the current study was to compare the expression of microRNAs (miRNAs) in exosomes derived from human bone mesenchymal stem cells (hBMSCs) with and without chondrogenic induction. Exosomes derived from hBMSCs were isolated and identified. Microarray analysis was performed to compare miRNA expression between exosomes derived from hBMSCs with and without chondrogenic induction, and quantitative real‐time polymerase chain reaction (qRT‐PCR) was used to verify the differentially expressed miRNAs. hBMSCs were transfected with miRNA mimic to extract miRNA‐overexpressed exosomes. The results showed that most exosomes exhibited a cup‐shaped or round‐shaped morphology with a diameter of approximately 50‐200 nm and expressed CD9 and CD63. We detected 141 miRNAs that were differentially expressed with and without chondrogenic induction by over a twofold change, including 35 upregulated miRNAs, such as miR‐1246, miR‐1290, miR‐193a‐5p, miR‐320c, and miR‐92a, and 106 downregulated miRNAs, such as miR‐377‐3p and miR‐6891‐5p. qRT‐PCR analysis validated these results. Exosomes derived from hBMSCs overexpressing miR‐320c were more efficient than normal exosomes derived from control hBMSCs at promoting osteoarthritis chondrocyte proliferation, down‐regulated matrix metallopeptidase 13 and up‐regulated (sex determining region Y)‐box 9 expression during hBMSC chondrogenic differentiation. In conclusion, we identified a group of upregulated miRNAs in exosomes derived from hBMSCs with chondrogenic induction that may play an important role in mesenchymal stem cell‐derived exosomes in cartilage regeneration and, ultimately, the treatment of arthritis. We demonstrated the potential of these modified exosomes in the development of novel therapeutic strategies. Abstract : We performed microarray analysis compare miRNA expression between exosomes derived from hBMSCs with and without chondrogenic induction. We identified a group of upregulated miRNAs in exosomes derived from hBMSCs with chondrogenic induction that may play an important role in mesenchymal stem cell‐derived exosomes in cartilage regeneration and, ultimately, the treatment of arthritis.